2010
DOI: 10.1155/2010/130506
|View full text |Cite
|
Sign up to set email alerts
|

On the Importance of the Aromatic Ring Parameter in Studies of the Solvolyses of Cinnamyl and Cinnamoyl Halides

Abstract: In solvolysis studies using Grunwald-Winstein plots, dispersions were observed for substrates with aromatic rings at the α-carbon. Several examples for the unimolecular solvolysis of monoaryl benzylic derivatives and related diaryl- or naphthyl- substituted derivatives have now been reported, where the application of the aromatic ring parameter (I) removes this dispersion. A recent claim suggesting the presence of an appreciable nucleophilic component to the I scale, has now been shown, in a review of the solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…In water distillation method, rose aromatic water contains very low amounts of (below 0.1%) essential oil and its main component is phenylethyl alcohol [ 4 , 10 16 ]. Double distillation method is used as a traditional method.…”
Section: Introductionmentioning
confidence: 99%
“…In water distillation method, rose aromatic water contains very low amounts of (below 0.1%) essential oil and its main component is phenylethyl alcohol [ 4 , 10 16 ]. Double distillation method is used as a traditional method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with equation 2 an h value of 0.42 ± 0.15 signified that there was minimal charge dispersion into the aromatic ring during the formation of the thioacylium transition state that was stabilized by intense rear-side nucleophilic solvation (as indicated by the large l value). These sensitivity values are now considered typical [2,7,23,27,29,30,33,34,49,56] for substrates believed to solvolyze with the formation of an acylium or a thioacylium ion in the transition state.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was demonstrated [2,12,14,15,18,20,21,2327] that dual reaction channels occurring simultaneously in a side-by-side fashion are possible in some alkyl and aryl chloroformate esters, and that the highly ionizing aqueous 2,2,2,-trifluoethanol (TFE) and 1,1,1,3,3,3,-hexafluoro-2-propanol (HFIP) mixtures are shown [2,3,649,55,56,71–74] to be extremely important for meaningful treatments leading to analyses using the Grunwald-Winstein equations. To probe the possibility of an ionization pathway for 1 , we have raised the temperatures (so that the kinetic runs could be followed within a reasonable time frame) and in Table 1 have included 16 specific rates of solvolysis in six solvents with strong hydrogen bonding (highly ionizing) fluoroalcohol components.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review [27] of 30 highly hindered substrates not having appropriately placed π-electrons, we determined that in such substrates the sometimes positive and sometimes negative h values that Martins observed [26] is an artifact resulting from the multicollinearity that is present between the I values and a linear combination of N T and Y X values [27]. We have also just demonstrated that the I scale is very useful in studies of the solvolyses of compounds containing a double bond in the vicinity of any developing carbocation [28]. logfalse(k/kofalse)=mY+c logfalse(k/kofalse)=lN+mY+c logfalse(k/kofalse)=italicmY+hI+c logfalse(k/kofalse)=lN+mY+hI+c…”
Section: Introductionmentioning
confidence: 99%